Ambivalence in Wieteke Van Dort’s Geef Mij Maar Nasi Goreng - Putut Handoko; Hariyono; Cahyaningsih Pujimahanani (Ilomata International Journal of Social Science, 2021)
This research focuses on how ambivalence works within the case of a Surabaya born singer, Wieteke Van Dort through her song Geef Mij Maar Nasi Goreng. The colonial power that lasted the longest time in today Indonesia was the Dutch administration. The Dutch people living in this area, experienced ambivalence, as the result of the challenging condition and the process of adaption where it was completely enigma to the condition of the motherland. Therefore, this study is conducted as a challenge to dichotomy of western vs eastern division in which extremely opposes each other. This research was descriptive qualitative in nature. The theory of ambivalence proposed by Homi Bhabha was used as an underlying theory. Postcolonial approach was also applied in analyzing Wieteke Van Dort’s ambivalence. The data were in the form of lyrics of a song entitled Geef Mij Maar Nasi Goreng. The research findings prove that through the lyrics of Geef Mij Maar Nasi Goreng, Wieteke Van Dort experiences ambivalence through her complex feeling in being attracted to her “native” Surabaya and her repulsion on the inferior Javanese culture. The research also shows that the western people, through the life of Wieteke Van Dort through her song Geef Mij Maar Nasi Goreng, experience ambivalence. It challenges the notion of nativeness in a sense that Wieteke Van Dort, as a native of Surabaya by birth, is ironically rejected by the other natives because of the judgment by blood. Western people, represented by Wieteke Van Dort, truly experience ambivalence.